Optimizing the xWORM assay for monitoring hookworm larvae motility - Lennox-Bulow, Danica; Becker, Luke; Loukas, Alex; Seymour, Jamie; Smout, Michael (Frontiers in Parasitology, 2023)
Parasitic worms (helminths) infect almost all taxa across the animal kingdom, and pose significant challenges to public health and economies, particularly in developing countries. To address this problem, researchers have developed various tools to measure the motility and viability of helminths. However, the conditions used in anthelmintic screening assays are often not optimized, and can vary considerably between research teams. These unoptimized conditions may impact novel drug screens, as little is known about the effects of different conditions on the health of the target parasites. To improve future research, this study determined the effects of key assay parameters including, media type, media concentration, in-well parasite density, and assay duration on the infective third-stage larva (L3) of two types of hookworms, namely Nippostrongylus brasiliensis in rodents, and Necator americanus in humans. Conditions were screened over several days using the xCELLigence worm real-time motility assay (xWORM); a real-time impedance-based helminth motility assay using the xCELLigence system with 96-well microplates. While results varied depending on the species and media used, the study found that 500–1,000 L3/200-µL and a media concentration of 3.13–25% generally produced good to excellent assay conditions. The findings of this study can guide the future selection of xWORM assay parameters for novel drug trials involving these parasite species and serve as a suggested model for optimizing trial conditions for alternative parasite targets and assays.